Mejoramiento de la disponibilidad de riego y uso del agua en un predio del sitio del barrio Cabianga, parroquia Malacatos, cantón Loja. - Correa Tamayo, Jimmy Roberto (2022)
In the property of Mister Ángel Correa located in the Cabianga neighborhood, Malacatos parish, Loja canton, Loja province, it belongs to the Quillollaco geological formation, moderately undulating relief, where soils of the Entisol order have been developed, currently it is dedicated to agriculture; In order to achieve a better condition to supply the water resource to it, a sprinkler irrigation design was carried out for the cultivation of corn (Zea mays) in an area of 0.20 ha. The hydrophysical constants of the soil were evaluated such as: field capacity (CC), permanent wilting point (PMP), porosity, texture, apparent density and pH; for this, disturbed and undisturbed soil samples were taken, for the latter 100 cm3 Koppecky cylinders were used at a depth of 40 cm in relation to the root zone of the crop. Regarding the agronomic design, the water needs of the crop (phenological phase of development) were mainly determined using the indirect Penman-Monteith method proposed by FAO to obtain ETo from climatic data obtained from INHAMI meteorological yearbooks, from the Malacatos meteorological station; among them, temperature (maximum and minimum), wind speed, heliophany and relative humidity; The Kc curve was obtained based on research carried out by Ureña (2017), which allowed for the calculation of crop evapotranspiration (ETc). The irrigation parameters determined for the study area were irrigation sheet of 33.78 mm, irrigation frequency of 7 days and an irrigation time of 4.17 ≅ 4h. For the hydraulic design, the network of main, multiple (secondary) and lateral pipes was calculated, with nominal diameters of 63 mm, and 32 mm, the Hazen-Williams equation was used; For the calculation of the multi-outlet pipes and / or lateral branches, the Christiansen coefficient was used. Keywords: sprinkler irrigation, agronomic design, hydraulic design.